Laboratory Evaluation of a Fully Automated Chemiluminescence Immunoassay for Rapid Detection of HBsAg, Antibodies to HBsAg, and Antibodies to Hepatitis C Virus - Ismail, Nahed (American Society for Microbiology, 2004)
The performance of a fully automated, random access, enhanced chemiluminescence immunoassay (Ortho/ECi) for the detection of antibody to hepatitis C virus (HCV) (anti-HCV), HBsAg, and antibody to HBsAg (anti-HBsAg), in human serum was compared to a Abbott second-generation enzyme immunoassay (EIA 2.0). The Ortho/ECi assays employ an immunometric technique with enhanced chemiluminescence for optimal assay performance. With regard to the study of clinical laboratory performance, six groups of sera prescreened with Abbott EIAs were assayed: anti-HCV-negative samples (n = 318), anti-HCV-positive samples (n = 177), anti-HBsAg-negative samples (n = 241), anti-HBsAg-positive samples (n = 239), HBsAg-positive samples (n = 158), and HBsAg-negative samples (n = 312). Sera with discrepant results in the two serological assays were resolved by confirmatory tests. Sera with indeterminate results by one or more confirmatory tests were evaluated by reviewing medical records. The overall concordance between the Ortho/ECi assay and the Abbott EIA were 97.78, 93.54, and 97.66% for anti-HCV antibodies, anti-HBsAg antibodies, and HBsAg, respectively. After resolving the discrepancies, the specificities of the new assay for anti-HCV and anti-HBsAg antibodies and HBsAg were 98.1, 92.8, and 100%, respectively. The sensitivities of the new assay for anti-HCV, anti-HBsAg, and HBsAg were 100, 98.8, and 97.4%, respectively. In conclusion, The Ortho/ECi assays for diagnosis of HCV and hepatitis B virus (HBV) infections are highly specific and sensitive assays. The rapid turnaround time, random access, full automation, and high throughput make it an effective assay system for clinical laboratory diagnosis of HCV and HBV infections.